Asas Pendidikan Ki Hajar Dewantara Dalam Cerita Rakyat Bengkulu - Asip, Muhammad; Dwidarti, Fera; Wisataone, Voettie; Likus (FKIP Unirow Tuban, 2023)
Folklore is a cultural heritage that holds many implicit and explicit meanings. The Ministry of Education and Culture in 1982 published a book entitled